Cylindroma of the Breast: A Systematic Review of a Rare Disorder - Salati, Sajad Ahmad; Alsuwaydani, Saleh (Lietuvos chirurgija, 2025)
Introduction. Cylindroma of the breast is a rare disorder, and only a few cases have been reported in the literature. Due to its rarity, this article was drafted to study the cases published over the last decade and thereby try to explain the current patterns in clinical presentation, diagnosis, treatment, and outcomes. Methods. A systematic literature search was conducted through electronic databases applying the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Results. There were 9 case reports with 10 female patients, ranging in age from 55 to 80 years. Local excision was the most common modality of treatment. The outcome was excellent with no recurrence. Conclusion. Cylindroma of the breast is rare with an excellent prognosis. It needs to be kept in mind as a differential diagnosis of triple-negative breast tumours or the solid basaloid variant of adenoid cystic carcinoma to avoid unnecessary overtreatment with associated morbidity.